The Influence of Human Capital on Company Performance: A Preliminary Study of Telekom Malaysia (Journal of International Studies, 2020)
The telecommunication industry has entered a very competitive environment for the past few decades and the industry has been deregulated. The Malaysian government has established a vision to be a developed nation by year 2020 and the deregulation of telecommunication services is one of the most important steps towards achieving that vision. To achieve the aspiration and realise the vision of making Malaysia a developed nation, and to survive in this highly competitive and challenging business environment, Telekom Malaysia has to be competitive, dynamic and robust. With the advancement made in the telecommunication technology, with the formation of various forms of business coalitions between local telecommunication services operators and other worldclass telecommunication companies, the challenge for the business survival of Telekom Malaysia is inevitable. Thus Telekom Malaysia that holds 97% of the market share of the fixed telecommunication services, 39% of the mobile services and 54% of the internet customers in Malaysia customers (Malaysian Communication & Multimedia Commission, 2004) has to maximize the utilisation of Telekom Malaysia's resources, especially it's intellectual capital. As a former government department, Telekom Malaysia has inherited the 28,000 employees, all the systems, technologies, business network and customers of Jabatan Telekom Malaysia. In 1996, the value of the human capital in Telekom Malaysia which in this case refers to only the salaries and allowances to the employees, stood at RM 836 million and in 2003, the value of its human capital was RM 1,412 million, an increase by 69% within seven years (Telekom Malaysia Annual Report, 1996, 2003). That is only in term of salaries and allowances, how about long-term relationship, know-how and others? This means that the only way for Telekom Malaysia to have an edge over its competitors will be to develop and put greater the use of its intellectual assets.